Elastomeric Electrolyte for High Capacity and Long‐Cycle‐Life Solid‐State Lithium Metal Battery. Issue 4 (19th February 2023) - Zhou, Zekun; Tao, Zengren; Chen, Ruiyong; Liu, Zhen; He, Zhenhang; Zhong, Lei; Li, Xin; Chen, Guixiang; Zhang, Peng
Abstract: High room‐temperature ionic conductivity and good compatibility with lithium metal and cathode materials are prerequisites for solid‐state electrolytes used in lithium metal batteries. Here, the solid‐state polymer electrolytes (SSPE) are prepared by combining the traditional two‐roll milling technology with interface wetting. The as‐prepared electrolytes consisting of elastomer matrix and high‐mole‐loading of LiTFSI salt show a high room temperature ionic conductivity of 4.6×10 −4 S cm −1, a good electrochemical oxidation stability up to 5.08 V, and improved interface stability. These phenomena are rationalized with the formation of continuous ion conductive paths based on sophisticated structure characterization including synchrotron radiation Fourier‐transform infrared microscopy, wide‐ and small‐angle X‐ray scattering. Moreover, at room temperature, the Li||SSPE||LFP coin cell shows a high capacity (161.5 mAh g −1 at 0.1 C), long‐cycle‐life (retaining 50% capacity and 99.8% Coulombic efficiency after 2000 cycles), and good C‐rate compatibility up to 5 C. This study, therefore, provides a promising solid‐state electrolyte that meets both the electrochemical and mechanical requirements of practical lithium metal batteries. Abstract : This work develops a novel protocol for the scalable manufacturing of high‐performance elastomeric electrolytes. The elastomeric electrolytes enable the solid‐state lithium metal battery to show unprecedented performances. Their structure–property correlations have been deciphered based on synchrotron radiation micro‐infrared microscopy, X‐ray scattering, and electrochemical characterizations.